2017
DOI: 10.18203/2320-6012.ijrms20171235
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of esophageal cancer in tertiary care hospital in North India: a clinicopathological study

Abstract: Background: Esophageal cancer is one of the deadliest and eighth most common cancer worldwide. It is the sixth most common cause of cancer related deaths with developing nations making up more than 80% of total cases and deaths. The purpose of this study was to assess the histopathological pattern of esophageal cancer in our region.Methods: In our centre, we analyzed 101 cases of endoscopic esophageal biopsy proven cases of esophageal cancer from January 2014 to June 2016. In most of these cases, dysphagia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Almost all of the patients in this study were presented with dysphagia as a chief presenting complaint and dysphagia was also the most common indication for upper GI endoscopy. Vishal Gupta et al find same type of presentation in his study [16].…”
Section: The Sms Hospital Jaipur Experiencesupporting
confidence: 63%
“…Almost all of the patients in this study were presented with dysphagia as a chief presenting complaint and dysphagia was also the most common indication for upper GI endoscopy. Vishal Gupta et al find same type of presentation in his study [16].…”
Section: The Sms Hospital Jaipur Experiencesupporting
confidence: 63%
“…Vishal Gupta et al find same type of presentation in his study. 16 Most important risk factors associated with esophageal carcinoma are smoking (bidi, cigarette or both), tobacco chewing and misuse of alcohol. 17 Even only one factor is independently related to causation of esophageal carcinoma but when more than one risk factors present in any individual then risk will increase by many more times.…”
Section: Discussionmentioning
confidence: 99%
“…The lower third of the esophagus was most involved. And adenocarcinoma was found to be the most common histopathological subtype, which is not comparable with Gupta et al's study since Gupta et al found that the upper and middle third of the esophagus was most involved and squamous cell carcinoma was the most common histopathological subtype [12].…”
Section: Discussionmentioning
confidence: 53%